2011
DOI: 10.5551/jat.6866
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and Cardiovascular Disease in Japan

Abstract: The aim was to give on overview of the profile of cardiovascular disease, vascular pathology and the relationships between lifestyle and cardiovascular disease in Japanese. Compared with the United States and Europe, the higher mortality from stroke and lower mortality from coronary heart disease constitute a unique cardiovascular profile for Japan.A selective review of population-based pathology, trend and prospective cohort studies was performed to clarify the characteristics of cardiovascular disease and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
108
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 31 publications
0
108
0
3
Order By: Relevance
“…Also, habitual high fish consumption in Japan has been associated with lower risk of hypercholesterolemia and lower risk of CHD (ref. 208 ). Apart from the antiarrhythmic and antithrombotic effects of LC n-3 PUFA, their antiinflammatory effect is very important since inflammation is a substantial component of CVD (ref.…”
mentioning
confidence: 99%
“…Also, habitual high fish consumption in Japan has been associated with lower risk of hypercholesterolemia and lower risk of CHD (ref. 208 ). Apart from the antiarrhythmic and antithrombotic effects of LC n-3 PUFA, their antiinflammatory effect is very important since inflammation is a substantial component of CVD (ref.…”
mentioning
confidence: 99%
“…However, a recent study revealed that the decline in mortality due to coronary heart disease and stroke since the 1970s was notably smaller in men aged 30-49 in Tokyo and Osaka, and has plateaued. 28 In fact, the incidence of coronary heart disease has increased among middle-aged men in the suburbs of Osaka. These trends may explain why heart disease mortality was only slightly lower in the studied cities compared to the country as a whole, signaling a potential source of future problems.…”
Section: Discussionmentioning
confidence: 99%
“…26 Within this context, the substantially lower cerebrovascular disease mortality in urban Japan, also found in other studies, 27 may be due to a combination of protective factors. Urban Japanese diets typically have lower sodium, higher calcium, and higher animal protein than rural Japanese diets, 28 and cities tend to have better access to emergency health services that can help prevent fatal outcomes from stroke. 29 Similar factors may help explain the lower mortality due to heart disease in urban Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Japonya'da (2007 yılında) inmeye bağlı ölüm oranı erkeklerde 99,2 ve kadınlarda 102. 3 olarak bildirilmiştir (15). Türkiye'de inme insidansının 100 binde 175 olduğu, her yıl ortalama 125 bin yeni inme vakası geliştiği, sadece İstanbul'da her yıl 20-30 bin kişinin inme geçirdiği bildirilmektedir.…”
Section: Introductionunclassified